Psychological and sleep disturbances among first-line, second-line, and at home medical staff during the COVID-19 pandemic in Shanghai, China - Ping Wang; Xiaolei Shen; Yuhan Jiang; Li Wu; Jun Shen; Xin Nie; Wei Chen; Jianren Liu (Frontiers Media S.A., 2022)
ObjectivesMedical workers are prone to psychological and sleep disturbances during the coronavirus disease 2019 (COVID-19) pandemic. Little is known about the varying degrees of influence among vaccinated medical staff working in different positions. The current study is aimed to evaluate and compare depression, anxiety and sleep disturbances among first-line, second-line and at home vaccinated medical staff during the COVID-19 pandemic in Shanghai, China.MethodsA cross-sectional online survey was conducted in May 2022. In addition to demographic data, levels of depression, anxiety, sleep quality, and insomnia were measured using the Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), Pittsburgh Sleep Quality Index (PSQI), and Athens Insomnia Scale (AIS).ResultsA total of 236 vaccinated medical workers completed the questionnaires, including 85 first-line medical staff (FMS), 82 second-line medical staff (SMS) and 69 at home medical staff (HMS). The proportions of depressive symptoms, anxiety symptoms, poor sleep quality, and insomnia were 52.1, 44.1, 55.9, and 49.2%, respectively. Compared with HMS, medical staff at work (FMS and SMS) got significantly higher frequency of poor sleep quality (both p < 0.001), insomnia (both p < 0.001), depressive (p < 0.001 and p = 0.003, respectively) and anxiety symptoms (p < 0.001 and p = 0.002, respectively). Compared with SMS, FMS were more likely to have poor sleep quality (p = 0.020). Besides, nurses got significantly higher percentage of poor sleep quality (OR = 1.352, p = 0.016) and insomnia (OR = 1.243, p = 0.041) than doctors. Whereas, the proportion of anxiety symptoms was increased in females than in males (OR = 2.772, p = 0.008).ConclusionsPsychological and sleep disturbances are common among medical staff at work during the COVID-19 pandemic. More psychological intervention should be administrated for FMS, especially for nurses.